Le système électoral guatémaltèque : entre tentatives de réformes, nouvelles dynamiques et menaces autoritaires - Garance Robert (IdeAs)
The promises of the 1996 peace accords - including the agreement on constitutional and electoral reforms - and successive attempts at electoral reform were intended to bring about greater transparency and participation of historically marginalized sectors of society (particularly the working classes and indigenous peoples) in the political life of the country. However, the party system and political representation in general in Guatemala continues to be marked by a lack of openness, clientelism and corruption. The prospects for the 2023 elections tend to confirm a great institutional weakness and a very limited democratic representation, threaten by a return to authoritarian forms of power.